Advances in Manufacturing Technology Select Proceedings of ICAMT 2018 - Hiremath, Somashekhar S.; Shanmugam, N. Siva; Bapu, B. R. Ramesh (Lecture Notes in Mechanical Engineering, 2019)
This volume comprises select papers presented at the International Conference on Advances in Manufacturing Technology (ICAMT 2018). It includes contributions from different researchers and practitioners working in the field of advanced manufacturing technology. This book covers diverse topics of contemporary manufacturing technology including material processes, machine tools, cutting tools, robotics and automation, manufacturing systems, optimization technologies, 3D scanning and re-engineering, and 3D printing. Computer applications in design, analysis, and simulation tools for solving manufacturing problems at various levels starting from material designs to complex manufacturing systems are also discussed. This book will be useful for students, researchers, and practitioners working in the field of manufacturing technology. .